A NEW SPECIES OF DUBYAEA (ASTERACEAE) FROM THE BURMA/CHINA BORDER - Mamgain, S. K.; Rao, R. R. (Edinburgh Journal of Botany, 2008)
A new species of Dubyaea (Asteraceae), D. forrestii Mamgain & R.R.Rao, from the Burma/China border is described, illustrated and compared with D. atropurpurea. The affinities of the new species to Dubyaea atropurpurea are discussed.
Keywords: Burma; Dubyaea atropurpurea; Dubyaea forrestii